Last year in dispute: History and memory as frames teaching - Mendoza García, Jorge (2021)
The present paper discusses the historic facts of the past: things happen, people involved, stories. Then, we point to the idea of dominant narrative of history, a positivistic view. Next, there are arguments sustaining the vision for a collective memory. Both positions are confronted focusing in similarities and differences. There were more differences. Authors subscribe the collective memory vision, besides the ambiguous an inaccurate it results. Finally, as an exercise, this approach is applied to the Mexican case, so against the official version of the success story there are alternative visions more open and wide about the recent past events. This way, we obtain different narrative versions without taken some of them as the truth. As a result heroes are demythologized.